Efficacy and Treatment-Related Adverse Events of Romidepsin in PTCL Clinical Studies: A Systematic Review and Meta-Analysis - Du, Jun; Han, Xinle; Lin, Suwen; Qiu, Chen; Zhu, Lijun; Huang, Zoufang; Hou, Jian (Frontiers in Medicine, 2021)
Background: Peripheral T-cell lymphoma (PTCL) is an extensive class of biologically and clinically heterogeneous diseases with dismal outcomes. The histone deacetylase inhibitor (HDACi) romidepsin was approved for relapsed and refractory (R/R-PTCL) in 2011. This meta-analysis was performed to assess the efficacy and safety of romidepsin in PTCL. Methods: We searched for articles on the HDAC inhibitor romidepsin in the treatment of PTCL in Embase, Web of Science, and PubMed. The methodology is further detailed in PROSPERO (CRD42020213651, CRD42020213553). The 2-year overall survival (OS), 2-year progression-free survival (PFS) and their corresponding to 95% confidence intervals (CIs) were measured. Besides, corresponding 95% CIs were pooled for the complete response (CR), partial response (PR), duration of response (DoR), and risk of adverse events (AEs). Results: Eleven studies containing 388 patients were incorporate into the quantitative synthesis, of which R/R-PTCL patients were the dominant portion, accounting for 94.3% (366/388). For all studies, the CR rate was 20% (95% CI, 13%-27%, random effects model), and the PR rate was 18% (95% CI, 12%-25%, random effects model). The 2-year OS was 48% (95% CI, 38%-59%, fixed effects model), and the 2-year PFS was 17% (95% CI, 13%-21%, fixed effects model). There were no significant differences between romidepsin monotherapy and romidepsin plus additional drugs. Hematological toxicities, such as lymphopenia and granulocytopenia, remained the most continually happening grade 3 or higher AEs, accounting for 46% and 28%, respectively. None of the studies reported any drug-related mortality. Conclusions: Considering that most of the included patients had R/R-PTCL, the addition of romidepsin significantly enhance the efficacy (irrespective of hematopoietic stem cell transplantation (HSCT)), and AEs were tolerable. It is imperative to further expand the first-line application of romidepsin and carry out personalized therapy based on epigenomics, which will improve the survival of PTCL patients.